Preparação, caracterização e avaliação da biodegradabilidade de blendas de amido/quitosana/PVA - Gomes, Anida Maria Moraes (2008)
The objectives of this work were to develop, characterize physico-chemical and rheologicaly blend films of yam (Dioscorea esculenta L.), jalapa (Operculina tuberose Meisn.), taro (Colocassia esculenta L.) and cowpea (Vigna unguiculata (L.) Walp.) starches with chitosan and poly (ninyl alcohol) (PVA) and to evaluate its biodegradation in the soil. The mechanical properties of the starches varied to each other, indicating a different molecular organization among them. The films of bean atarch were the most expandable and resistant, while the ones of chinese yam were the most fragile and brittle. The analyses of FT-IR revealed certain interaction among the three components which can be verified by the improvements in the mechanical properties, solubility in water and the water vapor permeability of blends. The characteristics presented by the blend films showed that from the technological point of view they were inferior to the commercial films (LDPE) and inadequate for packing of humid products, but they can be useful in another applications. However from the ecological point of view, these materials were better than the synthetic films, because they were quickly degraded in the soil. The blends presented potential to be used in medical applications as wound healing in drug delivery, however is needed more studies for improvements of those characteristics. The jalapa and cowpea starches showed similar or superior characteristics to the yam, what place them as alternative in the elaboration of starch biofilms.